Television viewing time and risk of chronic kidney disease in adults: The AusDiab study - Lynch, B.; White, S.; Owen, N.; Healy, Genevieve; Chadban, S.; Atkins, R.; Dunstan, D. (Springer, 2010)
Background: Television viewing time independent of physical activity is associated with a number of chronic diseases and related risk factors; however, its relationship with chronic kidney disease is unknown. Purpose: The purpose of this study is to examine the cross-sectional and prospective relationships of television viewing time with biomarkers of chronic kidney disease. Methods: Participants of the Australian Diabetes, Obesity and Lifestyle Study attended the baseline (n=10,847) and 5-year follow-up (n=6,293) examination. Results: Television viewing was significantly associated with increased odds of prevalent albuminuria and low estimated glomerular filtration rate. In the gender-stratified analyses this pattern was seen for men, but not for women. In the longitudinal analyses, odds of de novo albuminuria and low estimated glomerular filtration rate were increased only in unadjusted models. Conclusions: Television viewing time may be directly related to markers of chronic kidney disease and through intertwined associated risk factors such as diabetes, hypertension, and obesity. © 2010 The Society of Behavioral Medicine.